An Analysis of Taylor Swift's Song Lyric The Man Using Feminist Literary Criticism Theory - Putu Ayu Diah Damayanti; Putu Lirishati Soethama; I Nyoman Udayana (Program Studi Pendidikan Bahasa Inggris, ISDIK Kie Raha Maluku Utara, 2023)
Feminism was developed to defend women's rights and roles in society. It is a result of the evolution of culture and social structure, which increasingly differentiate the roles of women and men. The differences between women and men give rise to discrimination, leading to harassment. It is because gender equality still becomes an important problem in the modern era. Related to this, a song is an effective medium for conveying a message. It is because the message will be communicated through the song's story. Many celebrities raise the issue of feminism in their work, one of which is the famous singer Taylor Swift. This study aims to learn about the role of women and social meaning in Taylor Swift's song lyric The Man. For instance, the perception of women in society, their position among men, and the daily discrimination they confront. The data in this study was derived from the lyrics of Taylor Swift's song The Man. The qualitative research method was used to analyze the data in this study. The lyrics of The Man's songs are analyzed utilizing feminist literary criticism theory as the guidelines. The findings show that this song contains many elements of feminism. It is because Taylor Swift, throughout this song, wants to express her concerns about discrimination and gender equality.